Interaction of Isoflavones and Endophyte-Infected Tall Fescue Seed Extract on Vasoactivity of Bovine Mesenteric Vasculature - Jia, Yang; Harmon, David L.; Flythe, Michael D.; Klotz, James L. (Frontiers in Nutrition, 2015)
It was hypothesized that isoflavones may attenuate ergot alkaloid-induced vasoconstriction and possibly alleviate diminished contractility of vasculature after exposure to ergot alkaloids. The objective of this study was to determine if prior incubation of bovine mesenteric vasculature with the isoflavones formononetin (F), biochanin A (B), or an ergovaline-containing tall fescue seed extract (EXT) and their combinations affect ergotamine (ERT) induced contractility. Multiple segments of mesenteric artery and vein supporting the ileal flange of the small intestine were collected from Angus heifers at slaughter (n=5, Bodyweight = 639 ±39 kg). Duplicates of each vessel type were incubated in tissue culture flasks at 37℃ with a 50-mL volume of Krebs-Henseleit buffer containing: only buffer (Control); or 1 × 10-6 M EXT; F; or B; and combinations of 1 × 10-6 M EXT+F; 1 × 10-6 M EXT+B; 1 × 10-6 M F+B; or 1 × 10-6 M EXT+F+B. After incubation for 2 h, sections were mounted in a multimyograph chamber. The ERT dose responses were normalized to 0.12 M KCl. Pretreatment with F, B, and F+B without EXT resulted in similar contractile responses to ERT in mesenteric artery and all incubations containing EXT resulted in a complete loss of vasoactivity to ERT. In mesenteric artery pretreated with EXT, treatments that contained B had higher contractile responses (P < 0.05) at ERT concentrations of 1 × 10-7 M and 5 × 10-7 M. Also, treatments containing B tended (P < 0.1) to have greater responses than treatments without B at ERT concentrations of 1 × 10-6 M, 5×10-6 M, and 5 × 10-5 M. In mesenteric vein pretreated with EXT, treatments containing F had greater contractile responses to ERT at 1 × 10-5 M, 5 × 10-5 M, and 1 × 10-4 M (P < 0.05). These data indicated that F and B at 1 × 10-6 M and their combination did not impact the overall contractile response to ERT in mesenteric vasculature. However, F and B may offset some of the vasoconstriction caused by prior exposure to ergot alkaloids.